DEVELOPMENT OF THE TEACHING MODULE NUMERATION LITERACY ABILITY OF THE CREATIVE PROBLEM SOLVING VII CLASS - Kurnia Sri Hamdayani; Suherman Suherman; Yerizon Yerizon; Arnellis Arnellis (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
The study is done because school has not yet had teaching modules that could facilitate numerical literacy ability. The purpose of this study is to produce cps teaching modules that can enhance valid, practical, and effective numerical literacy capabilities in ratio and proportion materials, as well as line and Angle materials. The teaching module can be used at middle school/MTs, researchers can deliver this product to other schools that need it. This research methodology uses development research methods. This study's methodologies included research and development. The educate module is developed utilizing a plomp (preliminary research, development or prototype, and absorbed phases). The preparatory step entails an assessment of needs, curriculum, concepts, and learners. The development stage contains prototypes I, II, III, and IV. The module has been deemed legitimate based on a 3.5 average for materials, language, and humanities. Next, based on the value module evaluations completed by learners and educators, they produce an average of 84.51 and 92.31 with practical criteria. Then the results of the mathematical numerical literacy capability test are obtained by an average of 85% with qualified criteria, this means that the teaching module based creative problems solving are effective to enhance the mathematical numerical literacy ability of learners. The results showed that the teaching module based on creative problems solving to improve mathematical numerical literacy ability is valid, pratis, and effective. Penelitian ini dilakukan karena di sekolah belum memiliki modul ajar yang dapat memfasilitasi kemampuan literasi numerasi matematis. Tujuan dari penelitian ini yaitu menghasilkan modul ajar berbasis CPS yang dapat meningkatkan kemampuan literasi numerasi matematis yang valid, praktis, dan efektif pada materi rasio dan proporsi, serta garis dan sudut. Modul ajar ini bisa digunakan pada sekolah tingkat SMP/MTs, peneliti bisa memberikan produk ini pada sekolah lain yang membutuhkan. Metodologi penelitian ini menggunakan metode penelitian pengembangan. Modul ajar yang dikembangkan dengan menggunakan model plomp (penelitian pendahuluan, pengembangan atau prototipe, dan tahap penyerapan). Tahap persiapan meliputi analisis kebutuhan, kurikulum, konsep, dan peserta didik. Tahap pengembangan berisi prototipe I, II, III, dan IV. Modul ajar telah dianggap sah berdasarkan rata-rata 3,5 untuk materi, bahasa, dan kegrafikan. Selanjutnya, berdasarkan nilai evaluasi modul ajar yang diisi oleh peserta didik dan pendidik menghasilkan rata-rata 84,51 dan 92,31 dengan kriteria praktis. Kemudian dari hasil tes kemampuan literasi numerasi matematis didapatkan rata-rata 85% dengan kriteria cakap, ini berarti modul ajar berbasis Creative Problem Solving efektif untuk meningkatkan kemampuan literasi numerasi matematis peserta didik. Hasil tersebut menunjukkan bahwa modul ajar berbasis Creative Problem Solving untuk meningkatkan kemampuan literasi numerasi matematis sudah valid, pratis, dan efektif.